Can Partial Oxygen Pressure of Urine be an Indicator for Tissue Perfusion? - Tosun, Mclis; Ulugol, Halim; Aksu, Ugur; Toraman, Fevzi (AVES, 2019)
Objective: None of the advanced monitorisation procedures, which are focusing only on the haemodynamic and blood gas parameters, are sufficient to estimate tissue perfusion adequately. The search for new parameters that are non-invasive and reliable to provide information about tissue hypoperfusion is significant. The purpose of the present study was to evaluate the relationship between urine partial pressure of oxygen (PuO2) and routine systemic tissue perfusion parameters in patients with sepsis-like syndrome and impaired cardiac pressure-volume relationship after an open cardiac surgery. Methods: The study was designed in 50 patients who had elective coronary bypass surgery. Patients were assessed for arterial lactate levels, arterial partial oxygen pressure (PaO2), cardiac output (CO) and PuO2 in bladder urine at 180, 360 and 540 min postoperatively. Results: Tissue perfusion parameters were found to be similar throughout the surgery in addition to no significant rise in plasma creatinine levels. PuO2 was found to be 91 +/- 22, 99 +/- 22 and 97 +/- 13 mmHg, respectively, at the time points described above. Any correlation between PuO2 and other measurements was not determined at any time points. Conclusion: The present study suggests that urine PuO2 has no relationship with routine systemic tissue perfusion parameters, such as PaO2, lactate levels and CO. In our opinion, since the COs of the patients were within the normal limits, and none of the patients developed renal injury, the present study might have been unable to determine any correlation. Further studies focused on patients with transient renal ischaemia are needed.
Keywords: Cardiac surgery; renal blood flow; urinary oxygen pressure